Reasoning text and its types (Eurasian Journal of Philology Science and Education, 2018)
The present article is a continuation of the cycle of scientific and methodological comments to the training material of the Educational-methodical complex of the discipline «Russian language» for the experimental 11th grade of the 12-year education model [1] and it contains the analysis of the functional-semantic type of speech reasoning as well as the guidelines for practical tasks from the textbook. It considers the typical composition of this type of speech and peculiarities of reasoning and evidence, explanations and reflections.